Study on Microwave Absorption Performance of Submicron SrFe12O19 Particles Prepared by Hydrothermal Method - Nga, Tran Thi Viet; Quang, Nguyen Van; Loan, To Thanh; Chung, Hoang Manh; Anh, Luong Ngoc (VNU Journal of Science: Mathematics - Physics, 2024)
: Strontium hexaferrite (SrFe 12 O 19 ) materials were synthesized through the hydrothermal method with conditions at R = (Fe 3+ + Sr 2+ )/(OH ̶ ) ratio of 2 to 4 ( R ratio of 1/2, 1/3 and 1/4 were, respectively abbreviated to M2, M3 and M4). R has been examined by employing Fe(NO 3 ) 3 and Sr(NO 3 ) 2 as the initial materials. The effects of R ratio on the structure, particle size, magnetic and microwave-absorbing properties of the samples were studied. The coercivity and saturation magnetization of M4 sample reach 5.2 kOe and 58.7 emu/g, respectively. The optimal reflection loss of the M4 at the thickness of 1.5 mm reached a value as large as - 48.27 dB in the frequency range of 2 to 18 GHz. The improvement in microwave absorption performance of M4 sample compared to M2 and M3 was mainly resulted from the increased magnetic properties with increasing R ratio.